28‐4: Investigation of Moiré Interference in Pinhole Matrix Fingerprint on Display Technology. Issue 1 (25th September 2020) - Zeng, Yang; Lu, Feng; Yao, Qijun; Yu, Haochi; Zhang, Qing; Su, Xiaoyue
Abstract : We have investigated the Moiré interference in pinhole based fingerprint on display technology. The origin of the phenomenon is identified as the interference between discrete OLED pixels and the object outline. A countermeasure is given to overcome its impact on the identification of miniature fingerprint features.